2019
DOI: 10.1002/mdc3.12871
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia with Vitamin E Deficiency with Predominant Cervical Dystonia

Abstract: View Supplementary Video 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Clinical phenotypes include progressive gait ataxia, movement disorders, are exia, dysarthria, epilepsy, pyramidal signs, impaired proprioception and vibration sense and sensory neuropathy [9,10]. Except cerebellar ataxia, our patient exhibited obvious head tremor, it reported head titubation was a distinguishing motor feature of AVED patients range from 37-73% [1,3] , cervical dystonia was also a unique feature of AVED [11]. Non-neurological symptoms include retinitis pigmentosa, macular degeneration and cardiomyopathy [12], but these symptoms were not found in our patient.…”
Section: Discussionmentioning
confidence: 62%
“…Clinical phenotypes include progressive gait ataxia, movement disorders, are exia, dysarthria, epilepsy, pyramidal signs, impaired proprioception and vibration sense and sensory neuropathy [9,10]. Except cerebellar ataxia, our patient exhibited obvious head tremor, it reported head titubation was a distinguishing motor feature of AVED patients range from 37-73% [1,3] , cervical dystonia was also a unique feature of AVED [11]. Non-neurological symptoms include retinitis pigmentosa, macular degeneration and cardiomyopathy [12], but these symptoms were not found in our patient.…”
Section: Discussionmentioning
confidence: 62%
“…1 Rarely, dystonia has been described as the initial symptom. 4 Our patient presented with a year of progressive worsening gait due to spasticity of the lower extremities. He also showed dystonia and slowed alternating movements.…”
Section: Discussionmentioning
confidence: 87%
“…Head titubation is frequently associated with this disease, but dystonic head tremor as the predominant symptom is infrequently reported. 1,[3][4][5] We report a biochemically and genetically proven case of early adult-onset AVED presenting with predominant cervical and upper-limb dystonic tremor and sensory predominant ataxia.…”
Section: Dear Editormentioning
confidence: 96%
“…In addition, they reviewed the literature and identified 10 additional cases of AVED in which dystonia was noted. Pradeep et al 5 reported two out of three siblings from a family with AVED who had predominant dystonic head tremor at onset followed by the development of other features of AVED. Subsequently, there are two additional reports 7,8 of dystonia in patients with AVED (Supplementary Table 1 in the online-only Data Supplement).…”
Section: Dear Editormentioning
confidence: 99%